Menelusuri Jejak Damai: Kontribusi Tokoh Agama dalam Mewujudkan Kehidupan Beragama yang Harmonis - Remita Nian Permata Zendrato (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
In the midst of a complex and diverse society, this article explores the role of religious figures in shaping a harmonious religious life. It focuses on their contributions to fostering tolerance, dispelling religious stereotypes, and promoting mutual understanding. Challenges involve the complexity of belief diversity, including a lack of understanding and differences in the interpretation of religious values. However, amid these challenges, there are opportunities to build a stronger foundation of diversity. The method employed is the exploration of books and journals as primary references. The main results indicate that religious figures play roles as spiritual leaders, conflict mediators, and advocates of moral values. Challenges are addressed through dialogue, understanding, and collaboration among religious communities. Strategies and initiatives of religious figures involve concrete steps such as organizing dialogues and social activities. Interreligious collaboration is described as a collective effort for tolerance and cooperation. Case studies illustrate how religious figures can create harmony through dialogue, mediation, and inclusion. This article supports the understanding of the role of religious figures in shaping a harmonious and inclusive religious life.